2018
DOI: 10.1186/s12967-018-1511-x
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of coagulation activation in early breast cancer: development of a prognostic model based on data from the real world setting

Abstract: BackgroundCancer and coagulation activation are tightly related. The extent to which factors related to both these pathologic conditions concur to patient prognosis intensely animates the inherent research areas. The study herein presented aimed to the development of a tool for the assessment and stratification of risk of death and disease recurrence in early breast cancer.MethodsBetween 2008 and 2010, two hundreds thirty-five (N: 235) patients diagnosed with stage I–IIA breast cancer were included. Data on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…However, we demonstrated that elevated TAT levels were present not only in metastatic PA patients but in majority of patients with pancreatic cancer at the time of diagnosis. The findings reported here are in agreement with recently published study of Mandoj et al, which found increased TAT plasma levels in 34.4% of women with early breast cancer, before any anticancer therapy [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, we demonstrated that elevated TAT levels were present not only in metastatic PA patients but in majority of patients with pancreatic cancer at the time of diagnosis. The findings reported here are in agreement with recently published study of Mandoj et al, which found increased TAT plasma levels in 34.4% of women with early breast cancer, before any anticancer therapy [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…This trial is well placed within a research pipeline on coagulation and cancer. It is primarily aimed at validating the prognostic accuracy of our previously developed prognostic model in an independent cohort of breast cancer patients [9]. The ARIAS trial has received formal approval by the IRB of the coordinating center.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior study, we identified patient-and disease-related characteristics with prognostic relevance and included them into a prognostic model which proved accuracy in risk assessment and stratification in reference to the survival outcomes assessed in a cohort of 235 breast cancer patients diagnosed and treated at the IRCCS Regina Elena National Cancer Institute (IRE) between 2008 and 2010 [9]. Age, pathologic T (pT), baseline circulating levels of D-dimer (DD) and factor VIII (FVIII) proved prognostically relevant in multivariate models of overall survival (OS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations